Peningkatan Hasil Belajar Siswa melalui Problem Based Learning: Studi Penelitian Tindakan Kelas pada Materi Ekosistem (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
Science education at the junior high school level demands learning strategies that encourage active student engagement as well as enhance conceptual understanding. The low learning outcomes of students in the science subject of ecosystem materials emphasizes the need for learning innovations that focus on student activities. This study aims to evaluate the effectiveness of the Problem Based Learning (PBL) learning model in improving the learning outcomes of grade VIII students of SMP Negeri 1 Tumpaan. The research was conducted in the form of Classroom Action Research with two cycles, each of which included the planning, implementation, observation, and reflection stages. The subjects of the study were 30 students of grade VIII. The research instrument is in the form of learning outcome tests given at the pre-cycle stage, post-test cycle I, and post-test cycle II. Data were analyzed using descriptive statistics and repeated measurement tests to ascertain the significance of improving learning outcomes. The results showed an increase in students' average scores from 58 in the pre-cycle to 75.33 in the first cycle, and 79.5 in the second cycle. The percentage of learning completeness also increased from 20% to 66.67% in the first cycle, and reached 80% in the second cycle. Repeated measurement analysis showed significant differences between stages with strong positive correlation values. These findings confirm that PBL is effective in improving science learning outcomes, encouraging active student involvement, and improving the equitable distribution of achievement in the classroom. This research has implications for the importance of implementing PBL as an innovative learning strategy in junior high schools to support the achievement of science literacy and 21st century skill development